Investigation on Low-Frequency Micro-Vibration Model of Air Spring With Auxiliary Chamber for Steel Plate Concrete Composite Structures - Longji, Zhu; Taiki, Saito; Heisha, Wenliuhan; Zilin, Zhong (Frontiers in Materials, 2022)
Steel plate concrete composite (SPCC) structure plays an essential role in modular construction, which has been widely applied in the floating foundation vibration reduction system. This study proposed a basis for designing an SPCC floating foundation vibration reduction system with an air spring as the main vibration isolation element. Based on the engineering thermodynamics and aerodynamics theories, the nonlinear state equations and dynamic equations of each component of the air spring with auxiliary chamber were established, respectively. According to the operational characteristics of the air spring, the equations were linearized by using the small deviation linearization method under the condition of small amplitude, and the linearized model of the dynamic stiffness of the air spring with an auxiliary chamber was therefore proposed. The reliability of the proposed method was proved by a floating foundation vibration test, which was performed in a solid-state quantum laboratory. The constitutive equations of an air spring model and an SPCC floating foundation model were incorporated into the STERA_3D software. The simulation results showed good agreement with the low-frequency micro-vibration region test data.